2018
DOI: 10.2147/ott.s158309
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of a long noncoding RNA-associated competing endogenous RNA network in colorectal cancer

Abstract: PurposeThis study was aimed to develop a lncRNA-associated competing endogenous RNA (ceRNA) network to provide further understanding of the ceRNA regulatory mechanism and pathogenesis in colorectal cancer (CRC).Patients and methodsExpression profiles of mRNAs, lncRNAs, and miRNAs, and clinical information for CRC patients were obtained from The Cancer Genome Atlas. The differentially expressed mRNAs, lncRNAs, and miRNAs (referred to as “DEmRNAs”, “DElncRNAs”, and “DEmiRNAs”, respectively) were screened out bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…System-level analysis is widely used to detect diseases. Recently, the ceRNA network has received substantial attention in various diseases, such as gastric cancer, colorectal cancer, and pancreatic cancer (13,35,36). However, research to date on ceRNA in DN is focused on a single lncRNA, a single miRNA, or an lncRNA-miRNA pair; there are no reports on the ceRNA network in DN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…System-level analysis is widely used to detect diseases. Recently, the ceRNA network has received substantial attention in various diseases, such as gastric cancer, colorectal cancer, and pancreatic cancer (13,35,36). However, research to date on ceRNA in DN is focused on a single lncRNA, a single miRNA, or an lncRNA-miRNA pair; there are no reports on the ceRNA network in DN.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of computational and experimental methods is a useful research approach for predicting and verifying ceRNA interactions (12). In addition, research has shown that changes in topologically critical ceRNAs are associated with the development of lung adenocarcinoma, colorectal cancer, and ovarian cancer (13)(14)(15). Thus, systematic ceRNA network analysis can significantly expand functional understanding of both coding and noncoding RNAs.…”
mentioning
confidence: 99%
“…Recently, an lncRNA/miRNA/mRNA interactome was reported based on CRC expression data from the TCGA database. These analyses illustrated a ceRNA network of 25 principal miRNAs and 64 lncRNAs, including CRNDE, H19, HULC and UCA1 [ 17 , 89 ]. As discussed below, UCA1 was reported to interact with 29 miRNAs in several types of cancers.…”
Section: Mechanisms Of Regulation By Long Non-coding Rnas In Cancementioning
confidence: 99%
“…These studies aimed at some genes including mRNA, miRNA, and lncRNA associated with the cancer and confirmed that some of genes serve important roles in treatment and prognosis. With the development of experimental studies and techniques for lncRNA discovery, lncRNA‐associated ceRNA networks have been constructed and analyzed in colorectal cancer, gastric cancer, and osteosarcoma . However, there existed fewer analysis of ceRNA network in hepatocellular carcinoma (HCC).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of experimental studies and techniques for lncRNA discovery, lncRNA-associated ceRNA networks have been constructed and analyzed in colorectal cancer, gastric cancer, and osteosarcoma. 13,16,17 However, there existed fewer analysis of ceRNA network in hepatocellular carcinoma (HCC).…”
Section: Introductionmentioning
confidence: 99%